In vivo vascularization of anisotropic channeled porous polylactide-based capsules for islet transplantation: the effects of scaffold architecture and implantation site - Kasoju, N; Kubies, Dana; Fábryová, Eva; Kříž, Jan; Kumorek, M. M; Sticová, Eva; Rypáček, František (Physiological research, 2015)
The replacement of pancreatic islets for the possible treatment of type 1 diabetes is limited by the extremely high oxygen demand of the islets. To this end, here we hypothesize to create a novel extra-hepatic highly-vascularized bioartificial cavity using a porous scaffold as a template and using the host body as a living bioreactor for subsequent islet transplantation. Polylactide-based capsular-shaped anisotropic channeled porous scaffolds were prepared by following the unidirectional thermally-induced phase separation technique, and were implanted under the skin and in the greater omentum of Brown Norway rats. Polyamide mesh-based isotropic regular porous capsules were used as the controls. After 4weeks, the implants were excised and analyzed by histology. The hematoxylin and eosin, as well as Masson's trichrome staining, revealed a) low or no infiltration of giant inflammatory cells in the implant, b) minor but insignificant fibrosis around the implant, c) guided infiltration of host cells in the test capsule in contrast to random cell infiltration in the control capsule, and d) relatively superior cell infiltration in the capsules implanted in the greater omentum than in the capsules implanted under the skin. Furthermore, the anti-CD31 immunohistochemistry staining revealed numerous vessels at the implant site, but mostly on the external surface of the capsules. Taken together, the current study, the first of its kind, is a significant step-forward towards engineering a bioartificial microenvironment for the transplantation of islets.
Keywords: tobolky; Anisotropy; anizotropie; buněčné mikroprostředí; Capsules; Animals; Islets of Langerhans Transplantation; Lactic Acid; potkani inbrední BN; Islets of Langerhans; Neovascularization, Physiologic; fyziologická neovaskularizace; krysa rodu Rattus; antigeny CD31; Rats; fibróza; Porosity; poréznost; tkáňové podpůrné struktury; Rats, Inbred BN; zvířata; kyselina polyglykolová; Platelet Endothelial Cell Adhesion Molecule-1; Fibrosis; Langerhansovy ostrůvky; kyselina mléčná; transplantace Langerhansových ostrůvků; Tissue Scaffolds; Polyglycolic Acid; Cellular Microenvironment